Interaction of polymers with amyloidogenic peptides - Abraham, Jancy Nixon; Nardin, Corinne (Polymer International, 2018)
With this review, the aim was to gather recent representative publications which describe the interaction of polymers with amyloidogenic peptides/proteins. When functional, these take part in for instance bacterial adhesion and biofilm formation. However, several of the peptides/proteins have been identified in various diseases. One of the current approaches to discover a cure against these relies on therapeutics which either prevent or accelerate peptide/protein aggregation and/or clear readily formed aggregates. Owing to the common interest of scientists from all disciplines to identify a cure against the diseases of public health concern, there are overwhelming numbers of publications dealing with these two approaches. Since amyloid aggregation could be regarded as a nucleated polymerization, which is an established mechanism of polymer self-assembly, we recently tackled the issue of amyloid aggregation using the theories and methods established in polymer science. In this review, we hence focus on gathering relevant and recent publications which describe the role of polymers in modulating the aggregation of amyloidogenic peptides/proteins. (c) 2017 Society of Chemical Industry
Keywords: amyloid; neurodegenerative diseases; Polymer; protein; Self-assembly

Governing dynamics and preferential binding of the AXH domain influence the aggregation pathway of Ataxin-1 - Tammara, Vaishnavi; Das, Atanu (Proteins-Structure Function and Bioinformatics, 2023)
The present state of understanding the mechanism of Spinocerebellar Ataxia-1, a fatal neurodegenerative disease linked to the protein Ataxin-1 (ATXN1), is baffled by a set of self-contradictory, and hence, inconclusive observations. This fallacy poses a bottleneck to the effective designing of curable drugs as the field is currently missing the specific druggable site. To understand the fundamentals of pathogenesis, we tried to decipher the intricacies of the extremely complicated landscape by targeting the relevant species that supposedly dictate the structure-function paradigm. The atomic-level description and characterization of the dynamism of the systems reveal the existence of structural polymorphism in all the leading stakeholders of the overall system. The very existence of conformational heterogeneity in every species creates numerous possible combinations of favorable interactions because of the variability in segmental cross-talks and hence claims its role in the choice of routes between functional activity and dysfunctional disease-causing aggregation. Despite this emergent configurational diversity, there is a common mode of operative intermolecular forces that dictates the extent of stability of all the multimeric complexes due to the localized population of a specific type of residue. The present research proposes a dynamic switch mechanism between aggregability and functional activity, based on the logical interpretation of the estimated variables, which is practically dictated by the effective concentration of the interacting species involved in the cell.
Keywords: Ataxin-1; molecular dynamics simulation; neurodegenerative diseases; Protein aggregation; protein misfolding disorders